Common folding processes of mini‐proteins: Partial formations of secondary structures initiate the immediate protein folding. Issue 11 (13th February 2017) - Harada, Ryuhei; Takano, Yu; Shigeta, Yasuteru
Abstract : The folding processes of mini‐proteins (FSD‐EY/FBPWW28 domain) were computationally investigated by an enhanced conformational sampling method. Through the analyses of trajectories, these mini‐proteins had multiple folding pathways different from a simple two‐state folding, and the multiple folding processes were initiated by partial formations of secondary structures. These findings can be used to understand the folding of large proteins, that is, which secondary structures are partially folded in the early process, and how the remaining parts are sequentially folded. It is found that FSD‐EY (α/β topology) folds by a simple diffusion‐collision mechanism, while the folding process of the FBPWW28 domain (all‐β topology) requires a modification of the diffusion‐collision theory to adequately treat the coil‐sheet transition for the β sheet formation. © 2017 Wiley Periodicals, Inc. Abstract : The folding processes of mini‐proteins (FSD‐EY/FBPWW28 domain) were computationally investigated. Through the analyses of trajectories, these mini‐proteins had multiple folding pathways, and their folding processes were initiated by partial formations of secondary structures, that is, FSD‐EY (α/β topology) folds by a simple diffusion‐collision mechanism, while the folding process of the FBPWW28 domain (all‐β topology) requires a modification of the diffusion‐collision theory to adequately treat the coil‐sheet transition for the β sheet formation.